Quality-Adjusted Price Measurement: A New Approach with Evidence from Semiconductors - Byrne, David M.; Kovak, Brian K.; Michaels, Ryan (The Review of Economics and Statistics, 2017)
Many markets exhibit price dispersion across suppliers of observationally identical goods. Statistical agencies typically assume this dispersion reflects unobserved quality, so standard price indexes do not incorporate price declines when buyers substitute toward lower-price suppliers. We show that long-run price differences across suppliers can be used to infer unobserved quality differences and propose an index that accommodates quality-adjusted price dispersion. Using transaction-level data on contract semiconductor manufacturing, we document substantial quality-adjusted price dispersion and confirm that a standard index is biased above our proposed index.